Effect of Telephone Counseling on Continuity and Duration of Breastfeeding Among Primiparus Women - Mandana Mirmohammadali; Seyed Ahmad Reza Raisi Dehkordi; Morvarid Ghassab Shirazi; Mehdi Raei; Ziba Raisi Dehkordi (حیات, 2012)
Background & Aim: Breast milk provides many healthy nutrients to infants. Support provided by health care provider has positive effects on duration of breastfeeding. The purpose of this study was to determine the effects of telephone counseling on continuity and duration of breastfeeding among primiparus women.Methods & Materials: This clinical trial was conducted on 140 primiparus women referred to the selected health centers of Tehran University of Medical Sciences in 2010. The participants were randlomly allocated into two equal groups (each: 70 indviduals). The participants in the intervention group received telephone counseling by one of the researchers. The control group received routine care. Data were collected using a questionnaire including demographic characteristics and a breastfeeding check list. Exclusive breastfeeding rates were recorded one and three months after childbirth in both groups. Also, the continuity and duration of exclusive breastfeeding were recored three months after childbirth in both groups. Data were analyzed using the Chi-square test, Fisher's exact test, standard logistic regression and linear regression in the SPSS-16 and the Win Pepi.Results: The average duration of exclusive breastfeeding in the intervention group (8.05±3.99) was significantly more than the control group (6.23±4.03) (P=0.008). In the third month of delivery, continuity of exclusive breastfeeding in the intervention group was more than the control group (P=0.03). Results also showed that telephone counseling was effective in the duration of exclusive breastfeeding (P=0.02).Conclusion: Telephone counseling was effective in continuity and duration of exclusive breastfeeding. Using this inexpensive and easy method can help to increase exclusive breastfeeding, especially in primiparus women.